Diabetes and acute bacterial skin and skin structure infections. (April 2021) - Falcone, Marco; Meier, Juris J; Marini, Maria Giulia; Caccialanza, Riccardo; Aguado, José María; Del Prato, Stefano; Menichetti, Francesco
Highlights: Acute bacterial skin and skin structures infections (ABSSSI) have high morbidity. Diabetic patients are at high risk of skin infections and poor outcome from ABSSSI. Multidrug resistance represents a clinical and therapeutic challenge. A multidisciplinary approach may favor clinical cure in diabetic patients with ABSSSI. Summary: Acute bacterial skin and skin structures infections (ABSSSIs) are associated with high morbidity, costs and mortality in patients with diabetes mellitus. Their appropriate management should include several figures and a well-organized approach. This review aims to highlight the interplay between diabetes and ABSSSIs and bring out the unmet clinical needs in this area. Pathogenetic mechanisms underlying the increased risk of ABSSSIs in diabetes mellitus are multifactorial: high glucose levels play a crucial pathogenetic role in the tissue damage and delayed clinical cure. Moreover, the presence of diabetes complications (neuropathy, vasculopathy) further complicates the management of ABSSSIs in patients with diabetes. Multidrug resistance organisms should be considered in this population based on patient risk factors and local epidemiology and etiological diagnosis should be obtained whenever possible. Moreover, drug-drug interactions and drug-related adverse events (such as nephrotoxicity) should be considered in the choice of antibiotic therapy. Reducing unnecessary hospitalizations and prolonged length of hospital stay is of primary importance now, more than ever. To achieve these objectives, a better knowledge of the interplay between acute and chronic hyperglycemia, multidrug resistant etiology, and short and long-term outcome is needed. Of importance, a multidisciplinary approach is crucial to achieve full recovery of these patients.